Investigating the Impact of Strategic Flexibility on Organizational Innovation - Ghorban-Bakhsh, Raheleh; Gholipour-Kanani, Kanani (International Review of Management and Marketing, 2018)
This research is practical in terms of purpose and descriptive – scrolling in terms of data gathering. To investigating the impact of strategic flexibility on innovation, this method was done among managers and staff of the cultural center of education (Ghalamchi). The total number of members in the statistical society is 212 managers of Ghalamchi institute. The sample size is 136 people using Morgan table and simple sampling method was used for sampling. Data were collected by questionnaires. The reliability of the questionnaire was measured using Cronbach’s alpha. Its value is 0/96 which indicates the high reliability of the questionnaire. In order to analyze the data, linear regression was used. Results showed that strategic flexibility has a positive and significant impact on knowledge management and organizational innovation. Strategic flexibility has a mediation role in organizational learning and innovation. Organizations need to increase their adaptive capacity by promoting knowledge management in order to build their resilience to addressing intra-organizational and environmental shocks. Also, knowledge management directly and indirectly affects organizational flexibility. Knowledge management system is influential on organizational change resulting from innovation in the organization. Although, innovation is considered as a competitive advantage, but nonetheless, in some cases, companies are failing to earn economic returns in this way. The result of the research shows that resource flexibility has a positive relationship with product innovation but is completely dependent on the company’s performance and it depends on the company’s strategic flexibility. So that, strategic flexibility has the greatest impact on manufacturing innovation and has the least impact on process innovation. Keywords: strategic flexibility, Innovation, Product innovation, Process innovation, Administrative innovation. JEL Classifications: O3, Q55